Positive electrode active material precursor for secondary battery, and positive electrode active material
By using the positive electrode active material precursor particles with core and shell structures in the lithium composite oxide positive electrode active material, the problems of volume changes, cracks and structural instability during the charging and discharging process of lithium composite oxide are solved, and a higher battery life and charge and discharge capacity are achieved.
Patent Information
- Application Number
- CN202411227260.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-08
- Filing Date
- 2024-09-03
- Publication Date
- 2025-03-11
AI Technical Summary
The existing lithium composite oxide positive electrode active substances have volume changes, cracks and structural instability problems during charging and discharging, resulting in deterioration of life characteristics.
The positive electrode active material precursor particles containing the core part and the shell part are used, the core part contains nickel and aluminum, and the shell part contains cobalt, so that oxygen production is reduced by inhibiting cationic mixture and maintaining the layered structure.
It effectively suppresses direct contact between the surface and the electrolyte, strengthens the main structure, reduces the amount of gas generated, and improves the battery life and charge and discharge capacity.
Smart Images

Figure HDA0005025001990000011 
Figure HDA0005025001990000021 
Figure HDA0005025001990000031
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material particle and a precursor particle thereof included in a positive electrode active material of a secondary battery, and more particularly, to a positive electrode active material precursor particle and a positive electrode active material particle for a secondary battery including a core part and a shell part. Background Art
[0002] With the development of portable mobile electronic devices such as smart phones, MP3 players, and tablet computers, the demand for secondary batteries capable of storing electric energy has increased explosively. In particular, with the emergence of electric vehicles, large and medium-sized energy storage systems, and portable devices that require high energy density, the demand for lithium secondary batteries is continuously increasing.
[0003] As a lithium composite oxide included in a positive electrode active material, a recently spotlighted material is lithium nickel manganese cobalt oxide Li(Ni x Co y Mn z )O2 (in this case, x, y, and z above are atomic fractions of respective independent oxide constituent elements, 0 < x ≤ 1, 0 < y ≤ 1, 0 < z ≤ 1, and 0 < x + y + z ≤ 1). Compared with LiCoO2 that has been actively studied and used as a positive electrode active material in the past, this positive electrode active material material has the advantage of generating a higher capacity, and has the advantage of being inexpensive due to a relatively small Co content.
[0004] However, with the insertion and extraction of lithium ions during charge and discharge, this lithium composite oxide is accompanied by volume changes. During charge and discharge, there are problems such as a sharp volume change in primary particles of the lithium composite oxide, or the generation of cracks in secondary particles with repeated charge and discharge, or the collapse of the crystal structure or crystal structure phase change.
[0005] In order to compensate for this drawback, as a positive electrode active material for a secondary battery, the demand for a nickel (Ni)-rich system - high nickel positive electrode active material with a Ni content of 60 mol% or more has started to increase.
[0006] However, although this nickel-rich positive electrode active material has the advantage of high energy density, with the increase in Ni content, due to the increase in structural instability caused by Li / Ni cation mixing, physical fracture of internal particles due to microcracks, and the aggravation of electrolyte depletion, etc., there is a problem that the life characteristics deteriorate sharply at room temperature and high temperature.
[0007] In addition, the structure becomes unstable due to the high Ni content, and the reaction with the electrolyte increases on the particle surface and interface, so there is a problem that a large amount of gas is released during repeated charge and discharge and the life characteristics are reduced. Summary of the invention
[0008] Technical issues
[0009] The present invention aims to provide a positive electrode active material precursor and a positive electrode active material, which inhibit direct contact between the surface and the electrolyte and have a reinforced bulk structure to reduce the amount of gas generated that directly affects the reduction of life.
[0010] The present invention aims to solve the problem that as the output of positive electrode active material precursors and positive electrode active materials in industry increases, it is difficult to ensure uniformity in coating and doping due to the nature of the process.
[0011] The present invention aims to provide a positive electrode active material precursor and a positive electrode active material, which can inhibit the generation of oxygen by inhibiting cation mixing and maintaining a layered structure.
[0012] Technical Solution
[0013] The positive electrode active material precursor particles of one embodiment of the present invention may include a core portion and a shell portion, the core portion may include nickel and aluminum (Al), the shell portion may include cobalt (Co), the molar percentage of nickel in the core portion may be greater than the molar percentage of nickel in the shell portion, the molar percentage of aluminum in the core portion may be greater than the molar percentage of aluminum in the shell portion, and the molar percentage of cobalt in the shell portion may be greater than the molar percentage of cobalt in the core portion.
[0014] As one embodiment, the shell portion of the positive electrode active material precursor particles may further contain nickel.
[0015] As one embodiment, the shell portion of the positive electrode active material precursor particles may further contain manganese (Mn).
[0016] As one embodiment, the shell portion of the positive electrode active material precursor particles may not contain aluminum.
[0017] As one embodiment, the core of the positive electrode active material precursor particles may not contain cobalt.
[0018] As one embodiment, the core of the positive electrode active material precursor particles may not contain manganese.
[0019] As one embodiment, the positive electrode active material precursor particles may include 0.05 mol % to 0.25 mol % of aluminum relative to the total amount of transition metals included in the positive electrode active material precursor particles.
[0020] As one embodiment, the positive electrode active material precursor particle may further include a concentration gradient portion having a concentration gradient of one or more transition metals between the core portion and the shell portion.
[0021] The positive electrode active material particles of one embodiment of the present invention may include a core portion and a shell portion, the core portion may contain nickel and aluminum, the shell portion may contain cobalt, the molar percentage of nickel in the core portion may be greater than the molar percentage of nickel in the shell portion, the molar percentage of aluminum in the core portion may be greater than the molar percentage of aluminum in the shell portion, and the molar percentage of cobalt in the shell portion may be greater than the molar percentage of cobalt in the core portion.
[0022] As an embodiment, the positive electrode active material particle may further include a concentration gradient portion having a concentration gradient of one or more transition metals between the core portion and the shell portion.
[0023] As one embodiment, the positive electrode active material particles may further include a coating oxide.
[0024] The positive electrode active material particles according to one embodiment of the present invention may be prepared from the positive electrode active material precursor particles described above.
[0025] As one embodiment, the positive electrode active material particles may further include a coating oxide.
[0026] The positive electrode according to one embodiment of the present invention may further include the positive electrode active material particles described above.
[0027] Effects of the Invention
[0028] As an effect, the present invention provides a positive electrode active material precursor and a positive electrode active material, which suppress direct contact between the surface and the electrolyte and have a reinforced main structure to reduce the amount of gas generated that directly affects the reduction of life.
[0029] As an effect, the present invention solves the problem that it is difficult to ensure uniformity of coating and doping due to process characteristics as the production of positive electrode active material precursors and positive electrode active materials in the industry increases.
[0030] As one effect, the present invention provides a positive electrode active material precursor and a positive electrode active material that can suppress the generation of oxygen by suppressing cation mixing and maintaining a layered structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The cross-sectional SEM image and EDX analysis results of the positive electrode active material precursor particles according to the examples of the present invention are shown.
[0032] Figure 2 The FWHM of the positive electrode active material particles of the comparative example and the example of the present invention is shown. (104) Analyze the results.
[0033] Figure 3 The results of analyzing the high-temperature life characteristics of batteries according to comparative examples and examples of the present invention are shown.
[0034] Figure 4 and Figure 5 The results of analyzing the amount of gas generated by batteries according to comparative examples and examples of the present invention are shown.
[0035] Figure 6 The FWHM of the positive electrode active material particles of the comparative example and the example of the present invention is shown. (104) Analyze the results.
[0036] Figure 7 and Figure 8 The results of charge and discharge capacity analysis of batteries according to comparative examples and examples of the present invention are shown.
[0037] Fig. 9 The results of analyzing the charge and discharge efficiency of batteries according to comparative examples and examples of the present invention are shown.
[0038] Fig.10 and Fig.11 The results of analyzing the amount of gas generated by batteries according to comparative examples and examples of the present invention are shown. DETAILED DESCRIPTION
[0039] Expressions such as "comprising" and the like used in this specification should be understood as open-ended terms implying the possibility of including other structures.
[0040] The terms "preferred" and "preferably" used in this specification refer to embodiments of the present invention that can provide specified advantages under specified circumstances. However, other embodiments are not intended to be excluded from the scope of the present invention.
[0041] Furthermore, unless the context specifically indicates otherwise, singular forms used in the specification and the appended claims may be intended to include plural forms as well.
[0042] On the other hand, the following technical features relate to an embodiment for achieving the above-mentioned desired effects of the present invention.
[0043] That is, the positive electrode active material precursor particles and the positive electrode active material particles according to one embodiment of the present invention include the technical features of one embodiment described below, thereby significantly improving battery characteristics when applied to a secondary battery.
[0044] The present invention relates to positive electrode active material particles and precursor particles contained in the positive electrode active material of a secondary battery. The type of secondary battery is not limited, as long as it is a battery that can convert external electrical energy into chemical energy and store it for reuse. As a more preferred embodiment, the present invention may relate to positive electrode active material particles and precursor particles contained in the positive electrode active material of a lithium ion secondary battery.
[0045] First, the positive electrode active material precursor particles of the present invention will be described.
[0046] The positive electrode active material precursor particles according to one embodiment of the present invention may contain nickel.
[0047] As one embodiment, the positive electrode active material precursor particles may be nickel-based hydroxide.
[0048] As one embodiment, the nickel-based hydroxide may be represented by the following Chemical Formula 1.
[0049] Chemical formula 1:
[0050] Ni x Co y M 1-x-y (OH)2
[0051] In the above Chemical Formula 1, M is selected from the group consisting of Zr, Mn, Al, B, S, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr and combinations thereof, and 0.5≤x≤1.0, 0.0≤y≤0.4, and 0.0≤1-xy≤0.4.
[0052] As one embodiment, the nickel-based hydroxide may be represented by the following Chemical Formula 1-1.
[0053] Chemical formula 1-1:
[0054] Ni x’ Co y’ M1 z’ M2 1-x’-y’-z’ (OH)2
[0055] In the above chemical formula 1-1, M1 is Al or Mn, M2 is selected from the group consisting of Zr, B, S, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr and combinations thereof, and 0.5≤x'≤1.0, 0.0≤y'≤0.4, 0.0≤z'≤0.4, 0.0≤1-x'-y'-z'≤0.4.
[0056] As one embodiment, in the nickel-based hydroxide, x and / or x' representing the molar percentage of nickel relative to the total molar percentage of transition metals may be 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. In particular, it may be a high nickel hydroxide in which x and / or x' is 0.8 or more or 0.9 or more.
[0057] As one embodiment, in the nickel-based hydroxide, y and / or y' representing the molar percentage of cobalt relative to the total molar percentage of transition metals may be 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.
[0058] The positive electrode active material precursor particles according to one embodiment of the present invention include a core portion and a shell portion.
[0059] As one embodiment, the core of the positive electrode active material precursor particles may include nickel and aluminum.
[0060] Furthermore, as an embodiment, the molar percentage of nickel in the core of the positive electrode active material precursor particle may be greater than the molar percentage of nickel in the shell.
[0061] Furthermore, as one embodiment, the molar percentage of aluminum in the core of the positive electrode active material precursor particle may be greater than the molar percentage of aluminum in the shell.
[0062] Furthermore, as one embodiment, the shell portion of the positive electrode active material precursor particles may not contain aluminum.
[0063] Furthermore, as one embodiment, the shell portion of the positive electrode active material precursor particles may contain cobalt.
[0064] Furthermore, as one embodiment, the molar percentage of cobalt in the shell of the positive electrode active material precursor particle may be greater than the molar percentage of cobalt in the core.
[0065] Furthermore, as one embodiment, the core of the positive electrode active material precursor particles may not contain cobalt.
[0066] Furthermore, as one embodiment, the shell portion of the positive electrode active material precursor particles may contain nickel.
[0067] Furthermore, as one embodiment, the shell portion of the positive electrode active material precursor particles may contain manganese.
[0068] Furthermore, as one embodiment, the core of the positive electrode active material precursor particles may not contain manganese.
[0069] For the "positive electrode active material precursor particles" of this specification, the molar percentage value of the specific transition metal in the core portion refers to the molar percentage value of the specific transition metal relative to the total amount of the transition metal contained in the core portion. In addition, the molar percentage value of the specific transition metal in the shell portion refers to the molar percentage value of the specific transition metal relative to the total amount of the transition metal contained in the shell portion.
[0070] The cathode active material precursor particles of the present invention include a core portion and a shell portion having different compositions, and are prepared by increasing the molar concentration of aluminum in the core portion compared to the shell portion, or containing aluminum only in the core portion in addition to the shell portion.
[0071] In the past, a method of strengthening the main structure by doping with specific transition metal elements was used to reduce the generation of gases that directly affect the life of the positive electrode active material. To this end, after preparing the lithium composite oxide, these transition metal elements are coated on the surface and sintered to diffuse into the structure, or these transition metal elements are added during sintering with the lithium compound to diffuse into the structure for doping. However, with the increase in the production of positive electrode active material precursors and positive electrode active materials in the industry, there is a problem that it is difficult to ensure the uniformity of coating and doping due to process characteristics.
[0072] Therefore, in the present invention, in the step of preparing the precursor, aluminum is uniformly doped in the core portion by doping more aluminum in the core portion than in the shell portion, or by doping aluminum only in the core portion in addition to the shell portion.
[0073] The present invention can uniformly dope aluminum into the core of the positive electrode active material precursor particles, so that when preparing the positive electrode active material particles, Al 3+ The form is uniformly located in the lithium (Li) layer or transition metal layer, which can improve the capacity by suppressing cation mixing.
[0074] Furthermore, the present invention can be achieved by adding Al 3+ Electrochemically inert cations are uniformly placed in the core to further suppress oxygen generation.
[0075] Furthermore, the positive electrode active material precursor particles of the present invention maximize the effects as described above by increasing the molar concentration of cobalt in the shell portion compared to the core portion, or containing cobalt only in the shell portion in addition to the core portion, or increasing the molar concentration of nickel in the core portion compared to the shell portion, or increasing the molar concentration of manganese in the shell portion compared to the core portion, or containing manganese only in the shell portion in addition to the core portion.
[0076] As described above, the present invention controls the composition of the core and shell when preparing positive active material precursor particles and uniformly dopes aluminum into the core of the precursor particles, thereby further improving battery characteristics when the positive active material prepared in this way is applied to batteries.
[0077] Relative to the total amount of transition metals contained in the positive active material precursor particles of the present invention, the molar percentage value of aluminum may be 0.25 mole percent or less, 0.2 mole percent or less, 0.15 mole percent or less, 0.05 mole percent or more, 0.06 mole percent or more, 0.07 mole percent or more, 0.08 mole percent or more, or 0.09 mole percent or more, more preferably, 0.07 mole percent to 0.2 mole percent, and more preferably, the battery characteristics may be further improved at 0.09 mole percent to 0.15 mole percent. When aluminum is doped with a specific content or more, the movement of Li ions is suppressed due to the Pilar effect, so the charge and discharge capacity may decrease instead. Moreover, when the aluminum content is too low, the above effect may be weak. Therefore, when aluminum is doped with a content within the above range, the effect of increased structural stability and increased charge and discharge capacity may occur.
[0078] The present invention can strengthen the structure and significantly inhibit gas generation during high-temperature storage by applying specific processes, applying specific doping materials and controlling the level of doping content.
[0079] In the core of the positive electrode active material precursor particle of the present invention, the molar percentage of nickel relative to the total amount of transition metal contained in the core may be 80 molar percent or more, 85 molar percent or more, 90 molar percent or more, or 95 molar percent or more.
[0080] In the shell portion of the positive electrode active material precursor particles of the present invention, the molar percentage value of nickel relative to the total amount of transition metal contained in the shell portion can be greater than 60 molar percent, greater than 65 molar percent, less than 85 molar percent, less than 80 molar percent or less than 75 molar percent.
[0081] In the shell of the positive electrode active material precursor particle of the present invention, the molar percentage of cobalt relative to the total amount of transition metal contained in the shell may be 40 molar percentage or less, 30 molar percentage or less, 10 molar percentage or more, or 20 molar percentage or more.
[0082] In the shell portion of the positive electrode active material precursor particle of the present invention, the molar percentage of manganese relative to the total amount of transition metals contained in the shell portion may be 20 molar percentage or less, 15 molar percentage or less, or 10 molar percentage or less.
[0083] In the present invention, the core and shell of the positive electrode active material precursor particles can be controlled to have the above contents, thereby strengthening the structure and significantly suppressing gas generation during high-temperature storage.
[0084] Furthermore, the present invention can stabilize the structure and significantly improve the charge and discharge capacity by mixing aluminum in a specific step of the precursor preparation stage and then mixing with a lithium compound for the first heat treatment at a temperature of 670°C to 700°C, more preferably, at a temperature of 680°C to 690°C.
[0085] As one embodiment, the average thickness of the core of the positive electrode active material precursor particles (average length from the center of the secondary particle to the core surface) may be 90%, 93%, 98% or 97% of the secondary particle radius.
[0086] As one embodiment, the average thickness of the core of the positive electrode active material precursor particles may be 4.5 μm or more, 5.0 μm or more, 5.5 μm or more, 7.0 μm or less, 6.5 μm or less, or 6.0 μm or less.
[0087] As one embodiment, the average thickness of the shell of the above-mentioned positive electrode active material precursor particles (the average length from the core surface of the secondary particles to the surface of the secondary particles or the average length from the outer surface of the concentration gradient portion of the secondary particles to the surface of the secondary particles) can be less than 10%, less than 5%, more than 2% or more than 3% of the radius of the secondary particles.
[0088] As one embodiment, the average thickness of the shell portion of the positive electrode active material precursor particles may be 0.10 μm or more, 0.15 μm or more, 0.20 μm or more, 0.35 μm or less, or 0.30 μm or less.
[0089] On the other hand, in the present specification, the "particle diameter" means the average diameter (D50) when the particles are spherical, and the "particle radius" means 1 / 2 of the above-mentioned "particle diameter".
[0090] The present invention can improve battery characteristics such as structural stability and life by adjusting the composition ratio of the core part and the shell part in the positive electrode active material precursor particles and adjusting the thickness of the core part and the shell part within the above range.
[0091] As an embodiment, the diameter of the positive electrode active material precursor particles may be 8 μm to 20 μm.
[0092] As one embodiment, the positive electrode active material precursor having the above-mentioned particle size may be used alone (single-modal type) or may be used together with small particles having a smaller particle size (double-modal type).
[0093] The positive electrode active material precursor particles of the present invention may further include a concentration gradient portion having a concentration gradient of one or more transition metals between the core portion and the shell portion.
[0094] As one embodiment, the average thickness of the concentration gradient portion of the above-mentioned positive electrode active material precursor particles (the average length from the core surface of the secondary particles to the outer surface of the concentration gradient portion of the secondary particles) can be less than 10%, less than 5%, more than 2% or more than 3% of the radius of the secondary particles.
[0095] As one embodiment, the average thickness of the concentration gradient portion of the positive electrode active material precursor particles may be 0.10 μm or more, 0.15 μm or more, 0.20 μm or more, 0.35 μm or less, or 0.30 μm or less.
[0096] As one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of cobalt increases from the core portion toward the shell portion.
[0097] Furthermore, as one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of nickel decreases from the core portion toward the shell portion.
[0098] Furthermore, as one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of manganese increases from the core portion toward the shell portion.
[0099] Furthermore, as one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of aluminum decreases from the core portion toward the shell portion.
[0100] Next, the positive electrode active material particles of the present invention will be described.
[0101] The positive electrode active material particles according to one embodiment of the present invention may be lithium-nickel composite oxides containing lithium, nickel, and oxygen.
[0102] As one embodiment, the positive electrode active material particles may contain cobalt.
[0103] As one embodiment, the positive electrode active material particles may contain manganese and / or aluminum.
[0104] As one embodiment, the positive electrode active material particles may be represented by the following Chemical Formula 2.
[0105] Chemical formula 2:
[0106] Li a Ni x Co y M 1-x-y O2
[0107] In the above Chemical Formula 2, M is selected from the group consisting of Zr, Mn, Al, B, S, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr and combinations thereof, and 0.9≤a≤1.2, 0.5≤x≤1.0, 0.0≤y≤0.4, and 0.0≤1-xy≤0.4.
[0108] As one embodiment, the positive electrode active material particles may be represented by the following Chemical Formula 2-1.
[0109] Chemical formula 2-1:
[0110] Li a’ Ni x’ Co y’ M1 z’ M2 1-x’-y’-z’ O2
[0111] In the above chemical formula 2-1, M1 is Al or Mn, M2 is selected from the group consisting of Zr, B, S, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr and combinations thereof, and 0.9≤a'≤1.2, 0.5≤x'≤1.0, 0.0≤y'≤0.4, 0.0≤z'≤0.4, 0.0≤1-x'-y'-z'≤0.4.
[0112] As one embodiment, in the positive electrode active material particles, a and / or a' representing the molar percentage of lithium relative to the total molar percentage of transition metals other than lithium may be 0.9 or more, 1.0 or more, 1.2 or less, 1.1 or less, or 1.05 or less.
[0113] As one embodiment, in the above-mentioned positive electrode active material particles, x and / or x' representing the molar percentage of nickel relative to the total molar percentage of transition metals other than lithium may be 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. In particular, it may be a high-nickel lithium composite oxide in which x and / or x' is 0.8 or more or 0.9 or more.
[0114] As one embodiment, in the positive electrode active material particles, y and / or y' representing the molar percentage of cobalt relative to the total molar percentage of transition metals excluding lithium may be 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.
[0115] The crystal structure of the positive electrode active material particles according to one embodiment of the present invention may be hexagonal α-NaFeO 2 (R-3m space group).
[0116] A positive electrode active material particle according to an embodiment of the present invention includes a core portion and a shell portion.
[0117] As one embodiment, the core of the positive electrode active material particle may include nickel and aluminum.
[0118] Furthermore, as an embodiment, the molar percentage of nickel in the core of the positive electrode active material particle may be greater than the molar percentage of nickel in the shell.
[0119] Furthermore, as an embodiment, the molar percentage of aluminum in the core of the positive electrode active material particle may be greater than the molar percentage of aluminum in the shell.
[0120] Furthermore, as one embodiment, the shell portion of the positive electrode active material particle may contain cobalt.
[0121] Furthermore, as an embodiment, the molar percentage of cobalt in the shell of the positive electrode active material particle may be greater than the molar percentage of cobalt in the core.
[0122] Furthermore, as one embodiment, the core of the positive electrode active material particles may not contain cobalt.
[0123] Furthermore, as one embodiment, the shell portion of the positive electrode active material particle may include nickel.
[0124] Furthermore, as one embodiment, the shell portion of the positive electrode active material particle may contain manganese.
[0125] Furthermore, as one embodiment, the core of the positive electrode active material particles may not contain manganese.
[0126] For the "positive electrode active material particles" in this specification, the molar percentage value of the specific transition metal in the core portion refers to the molar percentage value of the specific transition metal compared to the total amount of transition metals other than lithium contained in the core portion. In addition, the molar percentage value of the specific transition metal in the shell portion refers to the molar percentage value of the specific transition metal compared to the total amount of transition metals other than lithium contained in the shell portion.
[0127] The positive electrode active material particle of the present invention includes a core portion and a shell portion having different compositions, and can be prepared by increasing the molar concentration of aluminum in the core portion compared to the shell portion.
[0128] Furthermore, the cathode active material particles of the present invention are doped with more aluminum in the core portion than in the shell portion in the step of preparing a precursor, so that aluminum is uniformly doped in the core portion of the cathode active material particles.
[0129] Furthermore, the positive electrode active material particles of the present invention are doped with aluminum in the step of preparing the core of the precursor, so that aluminum is uniformly doped in the core of the positive electrode active material particles.
[0130] Furthermore, the positive electrode active material particles of the present invention maximize the effects as described above by increasing the molar concentration of cobalt in the shell portion compared to the core portion, or containing cobalt only in the shell portion in addition to the core portion, increasing the molar concentration of nickel in the core portion compared to the shell portion, or increasing the molar concentration of manganese in the shell portion compared to the core portion, or containing manganese only in the shell portion in addition to the core portion.
[0131] As one embodiment, in the core of the above-mentioned positive electrode active material, the molar percentage value of nickel relative to the total amount of transition metals contained in the core except lithium can be greater than 80 molar percent, greater than 85 molar percent, greater than 90 molar percent or greater than 95 molar percent.
[0132] As one embodiment, in the shell portion of the above-mentioned positive electrode active material, the molar percentage value of nickel relative to the total amount of transition metals other than lithium contained in the shell portion can be greater than 60 molar percent, greater than 65 molar percent, less than 85 molar percent, less than 80 molar percent or less than 75 molar percent.
[0133] As one embodiment, in the shell portion of the above-mentioned positive electrode active material, the molar percentage value of cobalt relative to the total amount of transition metals other than lithium contained in the shell portion can be less than 40 molar percent, less than 30 molar percent, more than 10 molar percent or more than 20 molar percent.
[0134] As an embodiment, in the shell portion of the positive electrode active material, the molar percentage of manganese relative to the total amount of transition metals other than lithium contained in the shell portion may be 20 molar percentage or less, 15 molar percentage or less, or 10 molar percentage or less.
[0135] In the present invention, the core and shell of the positive electrode active material particles can be controlled to have the above contents, thereby strengthening the structure and significantly suppressing gas generation during high-temperature storage.
[0136] As one embodiment, the positive electrode active material particles may be secondary particles formed by agglomeration of one or more primary particles.
[0137] As one embodiment, the primary particles may include one or more crystallites.
[0138] As one embodiment, the secondary particle of the positive electrode active material may be in the form of a single particle including one primary particle, and when the primary particle is composed of one crystallite, it may be in the form of a single crystal.
[0139] As another embodiment, the secondary particles of the positive electrode active material may be in the form of multiple particles or polycrystalline particles including two or more primary particles. More preferably, the secondary particles of the positive electrode active material may be in the form of multiple particles or polycrystalline particles agglomerated from more than 20 primary particles.
[0140] The present invention can stabilize the structure and significantly improve the charge and discharge capacity by applying a specific process, applying a specific doping material and controlling the level of the doping content when preparing the positive electrode active material particles.
[0141] As one embodiment, the FWHM value of the full width at half maximum (FWHM) of the (104) peak of the positive electrode active material particle of the present invention defined by the hexagonal lattice having the R-3m space group is shown. (104) The range of may be 0.17 or more, 0.18 or more, 0.19 or more, 0.23 or less, 0.22 or less, 0.21 or less, or 0.20 or less.
[0142] On the other hand, in the present invention, the above FWHM (104) Correction is performed using the following equation 1.
[0143] Relation 1: FWHM (104) =FWHM 粉末(powder)(104) -FWHM Si粉末(powder) (220)
[0144] (In the above equation 1, FWHM Si粉末(powder)(220) It represents the full width at half maximum (FWHM) of the (220) peak observed near 47.3° (2θ) in the XRD measurement value of Si powder.
[0145] During the XRD analysis process, the full width at half maximum (FWHM) value may deteriorate or produce errors depending on various variables such as the conditions of the analysis equipment, the X-ray source, and the measurement conditions. Therefore, as shown in the above relationship 1, correction is performed using the full width at half maximum (FWHM) of the Si powder (powder) used as the standard sample.
[0146] In the present invention, Si powder (product number 215619) produced by Sigma-Aldrich was used as Si powder.
[0147] In the present invention, X-ray diffraction (XRD) analysis is performed by using Cu Kα radiation. The measurement was performed using a Bruker D8 Advance diffractometer at a step size (° / step) of 0.01° / step and a measurement time of 0.1 s / step.
[0148] As one embodiment, the average thickness of the core of the positive electrode active material particles (average length from the center of the secondary particle to the core surface) can be more than 90%, more than 95%, less than 98% or less than 97% of the radius of the secondary particle.
[0149] As one embodiment, the average thickness of the shell of the above-mentioned positive electrode active material particles (the average length from the core surface of the secondary particles to the surface of the secondary particles or the average length from the outer surface of the concentration gradient portion of the secondary particles to the surface of the secondary particles) can be less than 10%, less than 5%, more than 2% or more than 3% of the radius of the secondary particles.
[0150] The present invention can further improve battery characteristics such as structural stability and life by adjusting the composition of the core and shell in the positive electrode active material particles and adjusting the thickness of the core and shell to the above range.
[0151] As one embodiment, the diameter of the positive electrode active material particles (secondary particles) may be 8 μm to 20 μm.
[0152] As an embodiment, the positive electrode active material particle may further include a concentration gradient portion having a concentration gradient of one or more transition metals between the core portion and the shell portion.
[0153] As one embodiment, the average thickness of the concentration gradient portion of the above-mentioned positive electrode active material particles (the average length from the core surface of the secondary particles to the outer surface of the concentration gradient portion of the secondary particles) can be less than 10%, less than 5%, more than 2% or more than 3% of the radius of the secondary particles.
[0154] As one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of cobalt increases from the core portion toward the shell portion.
[0155] Furthermore, as one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of nickel decreases from the core portion toward the shell portion.
[0156] Furthermore, as one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of manganese increases from the core portion toward the shell portion.
[0157] Furthermore, as one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of aluminum decreases from the core portion toward the shell portion.
[0158] The positive electrode active material particles according to one embodiment of the present invention can be prepared from the positive electrode active material precursor particles described above, and the characteristics of the positive electrode active material particles are as described above.
[0159] The positive electrode active material particles according to one embodiment of the present invention may further include a coating oxide.
[0160] As one embodiment, the coating oxide may be a coating oxide occupying at least a portion of the shell portion.
[0161] As one embodiment, the coating oxide may occupy at least a portion of one or more of the grain boundaries between primary particles in the positive electrode active material particles, the surfaces of the primary particles, and the surfaces of the secondary particles.
[0162] As one embodiment, the coating oxide may be represented by the following Chemical Formula 3.
[0163] Chemical formula 3:
[0164] Li p M3 q O r
[0165] In the above chemical formula 3, M3 is one or more selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, S, Ba, Ta, Sn, Hf, Gd and Nd, and 0≤p≤10,0 <q≤8,2≤r≤13。
[0166] As an example, in the above Chemical Formula 3, M3 refers to a coating element, and the above coating oxide may be an oxide in which lithium and the element represented by M3 are combined, or may be an oxide of M3.
[0167] As an example, the coating oxide may be Li p Co q O r , Li p W q O r , Li p Zr q O r , Li p Ti q O r , Li p Ni q O r , Lip Al q O r , Li p Mo q O r 、Co q O r 、Al q O r , W q O r 、Zr q O r 、Ti q O r , B q O r , Li p (W / Ti) q O r , Li p (W / Zr) q O r , Li p (W / Ti / Zr) q O r , Li p (W / Ti / B) q O r , but not limited to this.
[0168] The coating oxide may include a concentration gradient portion where the molar concentration of the element contained in the coating oxide changes. As an example, when the coating oxide includes lithium, the molar concentration of lithium may change. And, as an example, the molar concentration of one or more of M3 contained in the coating oxide may change.
[0169] As one embodiment, when the coating oxide occupies at least a portion of the surface area of the outermost primary particle forming the secondary particle, the concentration gradient portion may decrease or increase from the surface of the outermost primary particle forming the secondary particle toward the center of the secondary particle, or first increase and then decrease.
[0170] Furthermore, the concentration gradient portion may decrease or increase, or first increase and then decrease, from the surface of the primary particle forming the outermost periphery of the secondary particle toward the center of the primary particle.
[0171] As one embodiment, when the coating oxide occupies at least a portion of the surface region of the primary particle that does not form the outermost periphery of the secondary particle, it may decrease or increase, or first increase and then decrease, from the surface of the primary particle toward the center of the primary particle.
[0172] The coating oxide of one embodiment of the present invention improves the battery output characteristics due to high ion conductivity and protects the surface of the lithium composite oxide, thereby further improving the battery life. In addition, it can effectively reduce the residual lithium present on the surface of the lithium composite oxide and prevent side reactions caused by unreacted residual lithium.
[0173] As a more preferred embodiment, the coating oxide may include at least one selected from titanium (Ti), aluminum, zirconium (Zr) and boron (B).
[0174] As an embodiment, when the aluminum is applied, 0.5 mol% to 0.7 mol% of aluminum may be mixed with respect to the total amount of transition metals other than lithium contained in the positive electrode active material particles and heat treated. When aluminum is applied to the positive electrode active material particles uniformly doped with aluminum in the core portion and heat treated, aluminum may be uniformly doped throughout the positive electrode active material particles to further improve battery characteristics.
[0175] As one embodiment, when 0.5 mol % to 0.7 mol % of aluminum, 0.05 mol % to 0.2 mol % of zirconium (Zr), 0.5 mol % to 0.7 mol % of titanium (Ti) and 0.2 mol % to 0.3 mol % of boron (B) are mixed and coated relative to the total amount of transition metals other than lithium contained in the positive electrode active material particles, the battery characteristics can be further improved.
[0176] The method for preparing the positive electrode active material of the present invention is not limited as long as it has the above-mentioned technical features, but as a more preferred embodiment, it can be prepared as follows.
[0177] First, a compound containing aluminum and a compound containing a transition metal are mixed, and the compositions of the core part and the shell part are changed to prepare a hydroxide.
[0178] Next, the prepared hydroxide and lithium compound are mixed and subjected to a first heat treatment at a temperature of 670° C. to 690° C. to prepare an oxide.
[0179] As a further preparation embodiment, the prepared above oxide and coating oxide may be mixed and subjected to a second heat treatment at a temperature of 670°C to 690°C.
[0180] As a further preparation implementation, the oxide that has undergone the second heat treatment may be cleaned and then dried.
[0181] As a further preparation embodiment, the dried oxide and the coating oxide may be further mixed and subjected to a third heat treatment at a temperature of 250°C to 350°C.
[0182] On the other hand, the technical characteristics of the positive electrode active material precursor particles may be related to the average technical characteristics of a plurality of positive electrode active material precursor particles contained in the positive electrode active material precursor.
[0183] Furthermore, the technical characteristics of the positive electrode active material particles may be related to the average technical characteristics of a plurality of positive electrode active material particles contained in the positive electrode active material.
[0184] On the other hand, the meaning of “≤”, “above” or “below” described in the present invention can be replaced by the meaning of “<”, “greater than” or “less than”.
[0185] The positive electrode according to one embodiment of the present invention may include the positive electrode active material particles described above.
[0186] The positive electrode may have a known structure and be prepared according to a known preparation method except for the positive electrode active material particles. The binder, conductive material and / or solvent are not particularly limited as long as they can be used for the positive electrode collector of a secondary battery.
[0187] A secondary battery according to one embodiment of the present invention may include the positive electrode active material particles described above.
[0188] Specifically, the secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and an electrolyte between the positive electrode and the negative electrode, but there is no particular limitation as long as it can be used as a secondary battery.
[0189] Hereinafter, embodiments of the present invention will be described in more detail.
[0190] Preparation of hydroxide precursors
[0191] Example
[0192] Relative to the total amount of transition metals contained in the precursor particles, 90.8 mol % of NiSO4·6H2O was added to the reactor, and 0.1 mol % of Al2(SO4)3, 25 weight % of NaOH and 28 weight % of NH4OH were added and stirred.
[0193] Next, 2.7 mol % of NiSO4·6H2O, 5 mol % of CoSO4·7H2O, 1.4 mol % of MnSO4·H2O, 25 weight % of NaOH and 28 weight % of NH4OH were added to the total amount of transition metals contained in the precursor particles and stirred to prepare particles.
[0194] In this case, the temperature in the reactor was maintained at 58° C., and N 2 was added as an inert gas in the reactor to prevent the prepared particles from being oxidized.
[0195] After the reaction is completed, a filter press (F / P) device is used for washing and dehydration.
[0196] Finally, the dehydrated product was dried at 120° C. to prepare a hydroxide precursor having a composition of 93.5 mol % of Ni, 5 mol % of Co, 1.4 mol % of Mn, and 0.1 mol % of Al.
[0197] Comparative Example 1
[0198] 0.1 mol percent of Al2(SO4)3, 25 weight percent of NaOH and 28 weight percent of NH4OH were added to an aqueous solution mixed in a molar ratio of NiSO4·6H2O:CoSO4·6H2O:MnSO4·H2O=94:5:1 in a reactor and stirred to prepare particles.
[0199] A hydroxide precursor having a composition of 93.5 mol % of Ni, 5 mol % of Co, 1.4 mol % of Mn, and 0.1 mol % of Al was prepared by the same method as Example 1 except for the above.
[0200] Comparative Example 2
[0201] 90.9 mol % of NiSO 4 ·6H 2 O was added to the reactor with respect to the total amount of transition metals contained in the precursor particles, and 25 wt % of NaOH and 28 wt % of NH 4 OH were added and stirred.
[0202] Next, 2.7 mol % of NiSO4·6H2O, 5 mol % of CoSO4·7H2O, 1.4 mol % of MnSO4·H2O, 25 weight % of NaOH and 28 weight % of NH4OH were added to the total amount of transition metals contained in the precursor particles and stirred to prepare particles.
[0203] A hydroxide precursor having a composition of 93.6 mol % of Ni, 5 mol % of Co, and 1.4 mol % of Mn was prepared by the same method as in Example 1 except for the above.
[0204] Preparation of oxides
[0205] Example 1-1
[0206] The hydroxide precursor prepared in Example 1 was mixed with LiOH (Li / Metal molar ratio = 1.04) as a lithium raw material.
[0207] The above mixture was placed in a sintering furnace (O2, 670°C, 2°C / min, holding time 10 hours) for heat treatment, and then furnace cooling was performed to prepare an oxide.
[0208] Example 1-2
[0209] The oxide was prepared by the same preparation method as in Example 1-1, except that the heat treatment of the mixture in a sintering furnace at 680° C. was changed to that in Example 1-1, the heat treatment of the mixture in a sintering furnace at 670° C. was replaced.
[0210] Examples 1-3
[0211] The oxide was prepared by the same preparation method as in Example 1-1, except that the heat treatment of the mixture in the sintering furnace at 690° C. was changed to that in Example 1-1, the heat treatment of the mixture in the sintering furnace at 670° C. was replaced.
[0212] Examples 1-4
[0213] The oxide was prepared by the same preparation method as in Example 1-1, except that the heat treatment of the mixture in the sintering furnace at 700° C. was changed to that in Example 1-1, the heat treatment of the mixture in the sintering furnace at 670° C. was replaced.
[0214] Examples 1-5
[0215] The oxide was prepared by the same preparation method as in Example 1-1, except that the heat treatment of the mixture in the sintering furnace at 710° C. was changed to that in Example 1, the heat treatment of the mixture in the sintering furnace at 670° C. was replaced.
[0216] Comparative Example 1-1
[0217] An oxide was prepared by the same preparation method as in Example 1-1, except that the hydroxide precursor prepared in Comparative Example 1 was mixed instead of the hydroxide precursor prepared in Example 1.
[0218] Comparative Example 1-2
[0219] The oxide was prepared by the same preparation method as in Comparative Example 1-1, except that the heat treatment of the mixture in a sintering furnace at 680° C. was changed to that in a sintering furnace at 670° C.
[0220] Comparative Examples 1-3
[0221] The oxide was prepared by the same preparation method as in Comparative Example 1-1, except that the heat treatment of the mixture in the sintering furnace at 690° C. was changed to that in the sintering furnace at 670° C.
[0222] Comparative Examples 1-4
[0223] The oxide was prepared by the same preparation method as in Comparative Example 1-1, except that the heat treatment of the mixture in a sintering furnace at 700° C. was changed to that in a sintering furnace at 670° C.
[0224] Comparative Examples 1-5
[0225] The oxide was prepared by the same preparation method as in Comparative Example 1-1, except that the heat treatment of the mixture in a sintering furnace at 710° C. was changed to that in a sintering furnace at 670° C.
[0226] Comparative Example 2-1
[0227] An oxide was prepared by the same preparation method as in Example 1-1, except that the hydroxide precursor prepared in Comparative Example 2 was mixed instead of the hydroxide precursor prepared in Example 1.
[0228] Comparative Example 2-2
[0229] The oxide was prepared by the same preparation method as in Comparative Example 2-1, except that the heat treatment of the mixture in a sintering furnace at 680° C. was changed to that in a sintering furnace at 670° C.
[0230] Comparative Example 2-3
[0231] The oxide was prepared by the same preparation method as in Comparative Example 2-1, except that the heat treatment of the mixture in a sintering furnace at 690° C. was changed to that in a sintering furnace at 670° C.
[0232] Comparative Examples 2-4
[0233] The oxide was prepared by the same preparation method as in Comparative Example 2-1, except that the heat treatment of the mixture in a sintering furnace at 700° C. was changed to that in a sintering furnace at 670° C.
[0234] Comparative Examples 2-5
[0235] The oxide was prepared by the same preparation method as in Comparative Example 2-1, except that the heat treatment of the mixture in a sintering furnace at 710° C. was changed to that in a sintering furnace at 670° C.
[0236] Preparation of oxide coating
[0237] Example 1-1-1
[0238] The oxide prepared in the above Example 1-1 is mixed with 0.6 mol percent TiO2, 0.6 mol percent Al2O3, and 0.1 mol percent ZrO2, and then placed in a sintering furnace (O2, 675°C, 4.4°C / min, holding time 8 hours) for heat treatment.
[0239] The heat-treated oxides were classified and crushed, and then washed with distilled water for 1 hour and dried.
[0240] Next, H3BO3 was mixed to 0.235% of the weight of the above dried product, and then placed in a sintering furnace (O2, 300°C, 4.4°C / min, holding time 8 hours) for heat treatment and then naturally cooled to prepare a coating oxide.
[0241] Example 1-2-1
[0242] A coating oxide was prepared by the same preparation method as in the above Example 1-1-1, except that only the oxide prepared in the above Example 1-2 was mixed instead of the oxide prepared in the above Example 1-1.
[0243] Example 1-3-1
[0244] A coating oxide was prepared by the same preparation method as in the above Example 1-1-1, except that only the oxide prepared in the above Example 1-3 was mixed instead of the oxide prepared in the above Example 1-1.
[0245] Example 1-4-1
[0246] A coating oxide was prepared by the same preparation method as in the above Example 1-1-1, except that only the oxide prepared in the above Example 1-4 was mixed instead of the oxide prepared in the above Example 1-1.
[0247] Example 1-5-1
[0248] A coating oxide was prepared by the same preparation method as in the above Example 1-1-1, except that only the oxide prepared in the above Example 1-5 was mixed instead of the oxide prepared in the above Example 1-1.
[0249] Comparative Example 1-1-1
[0250] A coating oxide was prepared by the same preparation method as in Example 1-1-1, except that the oxide prepared in Comparative Example 1-1 was mixed instead of the oxide prepared in Example 1-1.
[0251] Comparative Example 1-2-1
[0252] A coating oxide was prepared by the same preparation method as in Example 1-1-1, except that the oxide prepared in Comparative Example 1-2 was mixed instead of the oxide prepared in Example 1-1.
[0253] Comparative Example 1-3-1
[0254] A coating oxide was prepared by the same preparation method as in Example 1-1-1, except that the oxide prepared in Comparative Example 1-3 was mixed instead of the oxide prepared in Example 1-1.
[0255] Comparative Example 1-4-1
[0256] A coating oxide was prepared by the same preparation method as in Example 1-1-1, except that the oxide prepared in Comparative Example 1-4 was mixed instead of the oxide prepared in Example 1-1.
[0257] Comparative Example 1-5-1
[0258] A coating oxide was prepared by the same preparation method as in Example 1-1-1, except that the oxide prepared in Comparative Example 1-5 was mixed instead of the oxide prepared in Example 1-1.
[0259] Comparative Example 2-1-1
[0260] A coating oxide was prepared by the same preparation method as in Example 1-1-1, except that the oxide prepared in Comparative Example 2-1 was mixed instead of the oxide prepared in Example 1-1.
[0261] Comparative Example 2-2-1
[0262] A coating oxide was prepared by the same preparation method as in Example 1-1-1, except that the oxide prepared in Comparative Example 2-2 was mixed instead of the oxide prepared in Example 1-1.
[0263] Comparative Example 2-3-1
[0264] A coating oxide was prepared by the same preparation method as in Example 1-1-1, except that the oxide prepared in Comparative Example 2-3 was mixed instead of the oxide prepared in Example 1-1.
[0265] Comparative Example 2-4-1
[0266] A coating oxide was prepared by the same preparation method as in Example 1-1-1, except that the oxide prepared in Comparative Example 2-4 was mixed instead of the oxide prepared in Example 1-1.
[0267] Comparative Example 2-5-1
[0268] A coating oxide was prepared by the same preparation method as in Example 1-1-1, except that the oxide prepared in Comparative Example 2-5 was mixed instead of the oxide prepared in Example 1-1.
[0269] Preparation of lithium secondary batteries
[0270] The positive electrode slurry was prepared by dispersing 94 weight percent of the positive electrode active material prepared according to the above embodiments and comparative examples, 3 weight percent of artificial graphite, and 3 weight percent of polyvinylidene fluoride (PVDF) binder into 3.5 g of N-methyl-2-pyrrolidone (NMP). The above positive electrode slurry was coated on an aluminum film with a thickness of 15 μm as a positive electrode collector and dried, and roll pressed to prepare a positive electrode. The loading level of the positive electrode was 7 mg / cm 2 , the electrode density is 3.2g / cm 3 .
[0271] For the above-mentioned positive electrode, lithium foil is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) is used as a separator, and a button cell is prepared according to a generally known preparation process using a liquid electrolyte containing 1.5 M LiPF6 in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7.
[0272] Experimental example
[0273] (1) Cross-sectional SEM images and EDX analysis
[0274] For the hydroxide precursor of Example 1, a cross section was obtained by polishing at a current of 380 μA for 1 hour and 30 minutes using a cross section polisher. A cross-sectional SEM image of the hydroxide precursor particles was obtained at a voltage of 2 kV using a JSM-7610FPlus (JEOL) field emission scanning electron microscope (FE-SEM), and then the concentration changes of transition metals obtained by linescanning were shown in FIG. Figure 1 middle.
[0275] According to the above Figure 1 From the SEM image of MgO2, it was confirmed that the core portion contained Ni and Al, and the shell portion contained Co and Mn.
[0276] (2) FWHM (104) analyze
[0277] For the positive electrode active materials of Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-5, the FWHM according to the first heat treatment temperature was measured. (104) The values are shown in Figure 2 Medium. FWHM (104) The measurement method is as described above.
[0278] According to the measurement results, in the case of the comparative example in which the composition of the core part and the shell part was not changed, although the same content of Al as that of the example was doped, a tendency of too little Al was shown.
[0279] (3) High temperature life characteristics analysis
[0280] The lithium secondary batteries of Example 1-1-1, Example 1-2-1, Example 1-3-1, Example 1-4-1, Example 1-5-1 and Comparative Example 1-1-1, Comparative Example 1-2-1, Comparative Example 1-3-1, Comparative Example 1-4-1 and Comparative Example 1-5-1 were charged and discharged twice under the conditions of a temperature of 25° C., a voltage range of 3.0 V to 4.3 V, and 0.1 C / 0.1 C, and charged and discharged once under the conditions of a temperature of 45° C., a voltage range of 3.0 V to 4.4 V, and 0.1 C / 0.1 C, and then charged and discharged 50 times under the conditions of a temperature of 45° C., a voltage range of 3.0 V to 4.4 V, and 1.0 C / 1.0 C, and then the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention rate; capacity retention) was measured and shown in FIG. Figure 3 middle.
[0281] The measurement results confirmed that, at the same firing temperature, the high temperature life characteristics of the examples were significantly improved compared to the comparative examples in which the compositions of the core and shell parts were not changed despite doping with the same amount of Al as in the examples.
[0282] (4) Analysis of gas generation
[0283] The lithium secondary batteries of Example 1-1-1 and Comparative Example 1-1-1 were charged to 4.25 V at a constant current of 0.2 C and then stored at 60° C. for 80 hours to measure the volume change of the lithium secondary batteries due to gas generation in the lithium secondary batteries. The volume increase rate, which is an indicator of gas generation, was measured and shown in FIG. Figure 4 and Figure 5 middle.
[0284] According to the measurement results, based on 300 cycle full battery evaluation, it was confirmed that the lifetime gas and storage gas generation rates of the examples were significantly reduced compared to the comparative examples in which the core and shell compositions were not changed despite doping with the same amount of Al as in the examples.
[0285] (5) FWHM (104) analysis
[0286] For the positive electrode active material particles of Examples 1-1 to 1-5 and Comparative Examples 2-1 to 2-5, the FWHM (104) values according to the first heat treatment temperature were measured and shown in FIG. Figure 6 The FWHM (104) determination method is as described above.
[0287] The measurement results confirmed that, at the same sintering temperature, the particle size of the example increased compared to the comparative example which was a core-shell structure not doped with Al.
[0288] (6)Charge and discharge capacity and efficiency analysis
[0289] For the lithium secondary batteries of the above-mentioned Examples 1-1-1, 1-2-1, 1-3-1, 1-4-1, 1-5-1 and Comparative Examples 2-1-1, 2-2-1, 2-3-1, 2-4-1 and 2-5-1, a charge-discharge test was performed using an electrochemical analyzer (Toyo, Toscat-3100) at a temperature of 25°C and a voltage range of 3.0V to 4.25V with a discharge rate of 0.2C, and the charge capacity and discharge capacity are shown in Figure 7 and Figure 8 middle.
[0290] The charge and discharge efficiencies were calculated using the measured charge and discharge capacities and are shown in FIG. Fig. 9 middle.
[0291] According to the measurement results, at the same sintering temperature, the discharge capacity of the Example was significantly improved compared with the comparative example which was a core-shell structure not doped with Al, and thus a significant improvement effect in charge and discharge efficiency was confirmed.
[0292] (7) Gas generation analysis
[0293] The lithium secondary batteries of Example 1-1-1 and Comparative Example 2-1-1 were charged to 4.25 V at a constant current of 0.2 C and then stored at 60° C. for 80 hours to measure the volume change of the lithium secondary batteries due to gas generation in the lithium secondary batteries. The volume increase rate, which is an indicator of gas generation, was measured and shown in FIG. Fig.10 and Fig.11 middle.
[0294] According to the measurement results, based on the full battery evaluation of 300 cycles, it was confirmed that the lifetime gas and storage gas generation rates of the examples were significantly reduced compared to the comparative examples of the core-shell structure not doped with Al.
Claims
1. A positive electrode active material precursor particle, characterized in that: It includes a core and a shell. The core portion includes nickel and aluminum. The shell portion includes cobalt, The molar percentage of nickel in the core is greater than the molar percentage of nickel in the shell. The molar percentage of aluminum in the core is greater than the molar percentage of aluminum in the shell. The molar percentage of cobalt in the shell is greater than the molar percentage of cobalt in the core. The molar percentage of the specific transition metal in the core portion refers to the molar percentage of the specific transition metal compared to the total amount of the transition metal contained in the core portion. The molar percentage value of the specific metal in the shell portion refers to the molar percentage value of the specific transition metal relative to the total amount of the transition metal contained in the shell portion.
2. The positive electrode active material precursor particles according to claim 1, characterized in that: The shell portion further includes nickel.
3. The positive electrode active material precursor particles according to claim 1, characterized in that: The shell portion further contains manganese.
4. The positive electrode active material precursor particles according to claim 1, characterized in that: The shell portion does not contain aluminum.
5. The positive electrode active material precursor particles according to claim 1, characterized in that: The core portion does not contain one or more selected from cobalt and manganese.
6. The positive electrode active material precursor particles according to claim 1, characterized in that: The content of aluminum is 0.05 mol % to 0.25 mol % relative to the total amount of transition metals contained in the positive electrode active material precursor particles.
7. The positive electrode active material precursor particles according to claim 1, characterized in that: A concentration gradient portion having a concentration gradient of at least one transition metal is included between the core portion and the shell portion.
8. A positive electrode active material particle, characterized in that: It includes a core and a shell. The core portion includes nickel and aluminum. The shell portion includes cobalt, The molar percentage of nickel in the core is greater than the molar percentage of nickel in the shell. The molar percentage of aluminum in the core is greater than the molar percentage of aluminum in the shell. The molar percentage of cobalt in the shell is greater than the molar percentage of cobalt in the core. The molar percentage of the specific transition metal in the core portion refers to the molar percentage of the specific transition metal compared to the total amount of transition metals other than lithium contained in the core portion. The molar percentage value of the specific metal in the shell portion refers to the molar percentage value of the specific transition metal relative to the total amount of transition metals other than lithium contained in the shell portion.
9. The positive electrode active material particle according to claim 8, characterized in that: A concentration gradient portion having a concentration gradient of at least one transition metal is included between the core portion and the shell portion.
10. The positive electrode active material particle according to claim 8, characterized in that: Also contains coating oxides.
11. A positive electrode active material particle, characterized in that: Prepared from the positive electrode active material precursor particles according to claim 1.
12. The positive electrode active material particle according to claim 11, characterized in that: Also contains coating oxides.
13. A positive electrode, characterized in that: Contains the positive electrode active material particles according to claim 8.